2019
DOI: 10.1186/s42834-019-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Emission evaluation on 3-hole and 4-hole nozzle diesel engine with Jatropha and Pongamia (Karanja) mixed bio oil

Abstract: The present study aims in developing an alternative energy solution for compression ignition engine with mixed bio oils from Jatropha and Pongamia (Karanja) vegetable. The high viscosity of the oil was reduced by preheating and transesterification process. The properties of the oil namely viscosity, density, calorific value and flash point were evaluated. The exhaust emissions of a single cylinder diesel engine were examined using 3 hole (3H) and 4 hole (4H) nozzle with 80:20 diesel and biodiesel ratio. The 3H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Author observed that, blend of 40% multi functional fuel additives exhibits minimal power drop and reduced emissions. Nagaraj et al (2019) conducted a study on Jatropa and Pongomia bio fuel in diesel engines with 3 and 4 hole nozzle diesel engines. Author conducted a study for 80:20 diesel and bio diesel ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Author observed that, blend of 40% multi functional fuel additives exhibits minimal power drop and reduced emissions. Nagaraj et al (2019) conducted a study on Jatropa and Pongomia bio fuel in diesel engines with 3 and 4 hole nozzle diesel engines. Author conducted a study for 80:20 diesel and bio diesel ratio.…”
Section: Introductionmentioning
confidence: 99%